CAP: Context-Aware Programming for Cyber Physical Systems - Gaur, Shashank (2019)
Context-awareness is a prominently desired feature in computing systems. Smartphones, smart cards or tags, wearables, sensor nodes, and many other devices enable a system to compute context for different users and environment. With ever increasing advances in hardware for such devices, the interactions with users are increasing every day. This enables the collection of a large amount of data about users, systems, and physical environment. With such data available to be leveraged, context-awareness will soon become a necessity. Such type of data collection happens most frequently in sensing applications enabled by wireless sensor network (WSN) devices. This paper discusses the concept of context for sensing applications, specifically related to Cyber Physical Systems (CPS). The paper highlights key aspects of context and its definition. This paper proposes, to the best of the author's knowledge, the first programming approach to build context-aware applications for WSN-based CPS. This paper provides a proof of concept for a framework to detect, manage and deploy context-aware applications.